Self assembled photonic crystals in solar cells - Yip, Chan Hoe (2014)
Colloidal self-assembly (CSA) has been harnessed to fabricate nanoscale ordered structures with unique optical property for photovoltaic application. The self-assembly technique enables the fabrication of 3D photonic band gap (PBG) structures with (i) tunable periodicity; (ii) variable number of period; and (iii) the inclusion of a defect layer in a colloidal crystal thin film to enhance light-matter interaction in a dye-sensitized solar cell (DSSC). The increase in electric field near the dielectric band edge, where the group velocity of light is slow and the density of states is high, and the localization of permitted states in the gap have increased the photo-excitation of a photosensitive dye in a DSSC. This results in the increased light harvesting efficiency of the solar cell. This study provides an insight into the changes in optical absorption of an atom when the space surrounding that atom is modified. Finally, the PBG structure is most effective when it can be embedded as a back reflector in a photovoltaic cell and where its huge interfacial area can enhance the active area for photocurrent generation.